Atrial fibrillation ablation long-term ESC-EHRA EORP AFA LT registry: in-hospital and 1-year follow-up findings in Italy. Issue 10 (October 2020) - Anselmino, Matteo; Ballatore, Andrea; Saglietto, Andrea; Stabile, Giuseppe; De Ponti, Roberto; Grimaldi, Massimo; Agricola, Pietro M.G.; Della Bella, Paolo; Tritto, Massimo; Pappone, Carlo; Calò, Leonardo; Bongiorni, Maria G.; et al.
Abstract : Aim: To report the Italian data deriving from the European Society of Cardiology-EURObservational Research Program atrial fibrillation ablation long-term registry. Methods and results: Ten Italian centers enrolled up to 50 consecutive patients undergoing atrial fibrillation ablation. Of the 318 patients included, 5 (1.6%) did not undergo catheter ablation, 1 had ablation partially done and 62 were lost at 1-year follow-up. Women were less represented (23.6%) and the median age was 60.0 years. A total of 195 patients (62.3%) suffered paroxysmal atrial fibrillation, whereas only 9 (2.9%) had long-standing persistent atrial fibrillation. Most Italian patients (92.3%) were symptomatic but suffering fewer symptomatic events than patients enrolled in other countries (median of two events in the month preceding the ablation vs. three, respectively; P < 0.0001). The main finding of the study is that the success rate at 1 year, with and without antiarrhythmic drugs, was 76.4%, consistently with other participating countries (73.4%). This result was obtained however, with a significantly lower prevalence of 1-year adverse events (7.3 vs. 16.6%, P < 0.0001). Procedure duration and fluoroscopy total time resulted as being shorter in Italy (145 vs. 160, P = 0.0005 and 16.9 vs. 20.0 min, P = 0.0018, respectively); however, the radiation dose per BSA was greater (37.5 vs. 26.0 mGy/cm 2, P = 0.0022). Conclusion: The demographic characteristics of patients undergoing atrial fibrillation ablation are similar to those reported in other countries. The success rate in Italy is consistent with those in other countries, whereas the complications rate is lower. Abstract : Supplemental Digital Content is available in the text